ISLAMIC CRIMINAL LAW AS A BRIDGE OF CONTENTION BETWEEN PUBLIC AND INDIVIDUAL INTEREST WITHIN RESTORATIVE JUSTICE - Fathurokhmandan, Ferry; Fauzi, Ahmad (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2015)
Restorative justice has been developing broadly in many countries as a new paradigm in the criminal law field.Â Following the necessity and global trend, Indonesia has made an effort to replace the current Juvenile Court Act (JCA) with the new one, called Juvenile Criminal Justice System Act (JCJSA), which utilizes diversion as a restorative justice program for juvenile delinquent which took into effect since July 2014. As a new paradigm, restorative justice has been criticized sporadically. One of the critics is how to balance public interest and individual interest when they are in conflict regarding the restorative justice settlement that reached by the victim and offender. The contention between the proponent and opponent of the restorative justice movement on this issue is remains unsolved up to present. This issue is also possible may be arise when the Indonesian government enforces JCJSA. As a Muslim-majority country, Indonesia has an opportunity to resolve the contention by offering Islamic Criminal Law (jinayat) as an approach method since restorative justice values exist also in Islamic criminal law. There are at least two notions why Islamic criminal law could relax the contention. Firstly, historically Islamic law ever existed in Indonesia. Secondly, restorative justice values exist in Islamic Criminal Law. This paper will try to portray restorative justice in Islamic criminal law point of view in order to mollify the contention.